2020
DOI: 10.1186/s12974-020-01999-8
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-carbinol regulates microglia homeostasis and protects the retina from degeneration

Abstract: Background Retinal degenerative diseases significantly contribute to visual impairment and blindness. Microglia reactivity is a hallmark of neurodegenerative diseases including retinal cell death and immunomodulation emerges as a therapeutic option. Indole-3-carbinol (I3C) is a natural ligand of aryl hydrocarbon receptor (AhR), with potent immunomodulatory properties. Here, we hypothesized that I3C may inhibit microglia reactivity and exert neuroprotective effects in the light-damaged murine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
5
25
0
Order By: Relevance
“…To highlight, the anti-inflammatory and antioxidant effects of this phytochemical compound in cultured BV-2 cells exposed to LPS are consistent and reinforce a recent report ( Khan and Langmann, 2020 ). Moreover, these findings on LPS assure that Hsp70 overexpression mitigates oxidative stress and inflammatory status ( Mazzei et al., 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…To highlight, the anti-inflammatory and antioxidant effects of this phytochemical compound in cultured BV-2 cells exposed to LPS are consistent and reinforce a recent report ( Khan and Langmann, 2020 ). Moreover, these findings on LPS assure that Hsp70 overexpression mitigates oxidative stress and inflammatory status ( Mazzei et al., 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that I3C has many biological effects on regulating autoimmunity and inflammation. I3C is considered to be a potential therapeutic agent for colitis 56 , systemic lupus erythematosus 57 , retinal degeneration 58 , cerebral ischemic stroke 59 , and Parkinson's disease 60 . Herein, both diosmin and I3C showed a significant therapeutic effect on cognitive deficits through AhR activation and NEP upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…AhR is a cytoplasmic receptor that exhibits numerous physiological functions in immune cells such as B cells, T cells, neutrophils, and macrophages (102). Emerging evidence suggests that I3C can be targeted to ameliorate diverse inflammatory and autoimmune conditions (103)(104)(105)(106). Furthermore, it is reported that I3C can immunoregulate macrophages by activating AhR (107).…”
Section: Therapeutic Approaches Affecting Both M1-and M2-like Macrophagesmentioning
confidence: 99%